Research education іn the context of cultural аpproach - Галицька Майя (Неперервна професійна освіта: теорія і практика, 2014)
The article deals with the relationship of the concepts of «culture» and «education». The author analyzes the views of local and foreign scientists who researched this issue. The author considers cultural approach as a conceptual basis for the modernization of educational content. We prove that the concept of cultural integrity bases of educational content based on the identity of education and culture, as reflected in the model of humanitarian, cultural and educational system.
Halytska Maiia Research education іn the context of cultural аpproach / Maiia Halytska // Неперервна професійна освіта: теорія і практика. - 2014. - Вип. 1/2. - С. 19-22.
Keywords: education; culture; cultural approach to education; cultural integrity of the foundations of education